2015
DOI: 10.1371/journal.pcbi.1004239
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the 2013–2014 Influenza Season Using Wikipedia

Abstract: Infectious diseases are one of the leading causes of morbidity and mortality around the world; thus, forecasting their impact is crucial for planning an effective response strategy. According to the Centers for Disease Control and Prevention (CDC), seasonal influenza affects 5% to 20% of the U.S. population and causes major economic impacts resulting from hospitalization and absenteeism. Understanding influenza dynamics and forecasting its impact is fundamental for developing prevention and mitigation strategi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 55 publications
2
142
0
Order By: Relevance
“…Many studies have assessed the use of internet-user activity data because they can produce real-time indicators [10][11][12][13][14][15][16][17][18]. Several data sources have been explored, including Wikipedia, Twitter or Google search-engine data.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many studies have assessed the use of internet-user activity data because they can produce real-time indicators [10][11][12][13][14][15][16][17][18]. Several data sources have been explored, including Wikipedia, Twitter or Google search-engine data.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…If a person can be tested during the incubation period, they can be quarantined and treated, which is the only effective response to infectious viral diseases, such as influenza. Differences between influenza infection and other viral diseases and intestinal diseases exist [24][25][26]. Diarrhea, nausea, and vomiting are often mistaken as influenza.…”
Section: Influenza Investigationmentioning
confidence: 99%
“…Hickmann et al (6) assessed Wikipedia hits to five articles that referred to influenza to forecast the actual number of cases that were reported to the Centers for Disease Control and Prevention (CDC) during the 2013-2014 influenza season. They showed that the number of hits to the website predicted the official number of cases before these were published by CDC (6). An evaluation of the accuracy of Wikipedia articles regarding microbiology has not been published.…”
Section: Microbiology Search Engines and The General Publicmentioning
confidence: 99%